Blockchains from a Distributed Computing Perspective. - HERLIHY, MAURICE (Communications of the ACM, 2019)
The article discusses the long-term scientific value of blockchain algorithms and systems and examines their future compared to modern currency. Information is included on similarities between blockchain algorithms and algorithms used in distributed computing.